A Putative Type II Secretion System Is Involved in Cellulose Utilization in Cytophaga hutchisonii - Wang, Xia; Han, Qingqing; Chen, Guanjun; Zhang, Weixin; Liu, Weifeng (Frontiers in Microbiology, 2017)
Cytophaga hutchinsonii is a gliding cellulolytic bacterium that degrades cellulose in a substrate contact-dependent manner. Specific proteins are speculated to be translocated to its extracellular milieu or outer membrane surface to participate in adhesion to cellulose and further digestion. In this study, we show that three orthologous genes encoding the major components (T2S-D, -F, and -G) of type II secretion system (T2SS) are involved in cellulose degradation but not in cell motility. The individual disruption of the three t2s genes results in a significantly retarded growth on cellobiose, regenerated amorphous cellulose, and Avicel cellulose. Enzymatic analyses demonstrate that, whereas the endoglucanase activity of the t2s mutant cells is increased, the β-glucosidase activity is remarkably reduced compared to that of WT cells. Further analyses reveal that the t2s mutant cells not only exhibit a different profile of cellulose-bound outer membrane proteins from that of wild-type cells, but also display a significant decrease in their capability to adhere to cellulose. These results indicate that a functional link exits between the putative T2SS and cellulose utilization in C. hutchinsonii, and thus provide a conceptual framework to understand the unique strategy deployed by C. hutchinsonii to assimilate cellulose.